Factor Structure of the Scale of Sensed Parental Competencies: Version for parents (ECPP-p) - Yannet Valencia-Chacón (Interacciones)
Background: This study examines the dimensionality of the parent version of the Scale of Sensed Parental Competencies (ECPP-p). The sample was composed of 227 parents (n = 227; M = 35.34, DE = 7.22) from Lima Metropolitan. Method: The structural analysis was conducted with confirmatory factor analysis using the estimator WLSMV according to the ordinal nature of the items on the scale. The original structure evaluated of five correlated dimensions: school involvement, personal dedication, shared leisure, counseling and guidance and assumption of the role of father or mother was confirmed. Results: An adequate fit was obtained to the model of five factors, X2 = 406.47, CFI = .96, TLI =0.95, RMSEA =0.068. The internal consistency coefficients were adequate for each of the dimensions ( w >0.80) ( α >0.70). Conclusion: The ECPP-p is an instrument that presents evidence of internal structure and reliability in the study sample.